Where academia and policy meet. - Gal, John (Policy Press, 2017)
Hough academia has the reputation of being removed from the world, in reality the worlds of the academy and politics meet frequently, and in a variety of ways--productive and unproductive. This book presents the results of the first major crossnational comparative study of academic engagement in the creation of social policy. It offers new empirical data from twelve countries across Europe, North America, and the Middle East, with each chapter providing a brief overview of social work and social work education in the country under consideration, then presenting new data on the interactions between scholars and policy makers there. --